Pengaruh Kepemimpinan dan Kompensasi Terhadap Kinerja Karyawan CV. Brothers Palembang - Tricayanti, Yulia; Roswaty, Roswaty; Rostiati, Neny (Jurnal Nasional Manajemen Pemasaran dan SDM, 2023)
This research aims to impressed leadership and compensation for employee performance at CV. Brothers Palembang. This type of research was descriptive quantitative. The data employed primary and secondary data. Data collection techniques using questionnaires. The sample in this study amounted to 44 employees. Data analysis utilized multiple linear regression. Based on the results of the T-test prove that leadership affect the employee performance partially. Based on the results of the F test that leadership and compensation have a simultaneous effect on employee performance. This research has the determination of 0.454 that was the coefficient. This R Square value indicates the contribution of leadership and compensation variables to employee performance variables is 45.4%. This research is expected to help the company as consideration for employee performance.